Fractional fuzzy based static var compensator control for damping enhancement of inter-area oscillations - Zabaiou, Tarik; Benayad, Khadidja (International Journal of Electrical and Computer Engineering (IJECE), 2025)
Over time, the insertion of flexible alternating current transmission system (FACTS) components in the power grid became primordial to maintain the overall system stability. This paper proposed an innovative approach called hybrid auxiliary damping control based wide-area measurements for the static var compensator (SVC). The presented controller is a fractional-order fuzzy proportional integral derivative (FOFPID). Its principal task is to damp inter-area low frequency oscillations (LFOs) and to improve the power system stability over the transient dynamics. Then, a metaheuristic grey wolf optimization (GWO) method is applied to adjust the controller’s gains. The SVC-based FOFPID control scheme is implemented in a two-area four- machine test system employing the rotor speed deviations of generators as input signal. A comparative analysis of the elaborated controller with the integer PID and the fractional-order PID (FOPID) is performed to emphasize its effectiveness under a three-phase perturbation. Furthermore, a load variation effect test is completed to attest the control strategy robustness. Based on dynamic simulation results and performance indices, the suggested controller shows its robustness and provides increased efficiency for inter- area oscillations damping.